The influence of blowing agent addition, talc filler content, and injection velocity on selected properties, surface state, and structure of polypropylene injection molded parts. Issue 1 (January 2020) - Palutkiewicz, Paweł; Trzaskalska, Milena; Bociąga, Elżbieta
The effects of blowing agent, talc, and injection velocity on properties of polypropylene molded parts were presented. Blowing agent was dosed to plastic in amounts 1–2% and talc 10–20%. The results of selected properties, such as weight, thickness, hardness, impact strength, tensile strength, and gloss, were presented. The article also presents microscopic investigations. The blowing agent and talc content have a large impact on mechanical properties and gloss of parts than addition of blowing agent. The use of the blowing agent in an amount of 2 wt% will allow the reduce injection cycle time by reducing the hold pressure and hold time. Addition of blowing agents lowers of tensile strength, hardness, impact strength, and significantly affected the gloss. Talc filler contributes to a significant increase in the weight of parts, a decrease in hardness, impact strength, and tensile strength. The injection velocity has no significant effect on parts properties.